Preparation, characterization and antioxidant activity of inclusion complex loaded with puerarin and corn peptide. (October 2022) - Zheng, Lijun; Xu, Hongjia; Hu, Hao; Ruan, Jingxin; Shi, Caihong; Cao, Jiaqing; Zhang, Xiangrong
Abstract: Puerarin with antioxidant ability has been applied in the food industry as well as in medicine. However, Puerarin is poorly soluble in water and is unstable at high temperatures. A new delivery system of puerarin-corn peptide-β-cyclodextrin (PA-CP-βCD) ternary complexes was developed in this study. The Taguchi design method was applied to optimize the preparation of the inclusion complex. PA-CP-βCD with an inclusion rate of 95.52% was achieved under stirring at 50 °C for 4 h, molar ratio of host and guest molecules of 2:1 and corn peptides of 40%. PA-CP-βCD dissolves faster in different media of pH 1.2, 4.5, 6.8, 7.4, and water than pure puerarin. Compared with free puerarin, the antioxidant activity and the stability of puerarin in PA-CP-βCD were significantly improved. In addition, the morphology of PA-CP-βCD was characterized by scanning electron microscopy (SEM). The X-ray diffractometry (XRD) and differential scanning calorimetry (DSC) results indicated that PA-CP-βCD was an amorphous form. Molecular docking analysis confirmed intermolecular hydrogen bonds between puerarin and β-cyclodextrin. This study provides a formulation design to enhance the solubility, stability and antioxidant activity of puerarin. Highlights: The optimal process of PA-CP-βCD was obtained by Taguchi orthogonal experimental design. Differential scanning calorimetry and X-ray diffractometry showed an amorphous state of PA-CP-IC. Molecular docking analysis confirmed the presence of intermolecular hydrogen bonds between puerarin and β-cyclodextrin. The PA-CP-βCD can be rapidly dissolved under different pH conditions, be applied for improving the stability and antioxidant activity of puerarin.